The TTG-Amphibolite Terrains of Arctic Fennoscandia: Infinite Networks of Amphibolite Metatexite-Diatexite Transitions - Halla, Jaana (Frontiers in Earth Science, 2020)
The Earth’s early basaltic crust converted episodically into felsic TTG (tonalite-trondhjemite-granodiorite) crust by unknown tectonic processes. To contribute to the debate on the possible tectonic settings of TTGs, this article illustrates and explains migmatite structures of Meso- to Neoarchean TTG-amphibolite terrains in Arctic Fennoscandia. The Lake Inari and Rommaeno complexes in northern Finland and West Troms Complex in northern Norway consist of folded and banded TTG gneisses with abundant amphibolite enclaves. The terrains show migmatite structures generated by in situ and in-source melting of amphibolites and repeated metatexite-diatexite transitions that form infinite and boundless interconnected networks over vast areas. The aim of this article is to show that the TTGs of these terrains represent coalesced in situ and in-source neosomes of amphibolite protoliths and are not similar to granitoids sensu stricto generated by modern-style plate tectonics. The structures of the TTG-amphibolite associations of Arctic Fennoscandia suggest intracrustal differentiation by syn-anatectic partial melting of amphibolites in deep parts of a thick mafic crust.